MENULIS KREATIF DAN PSIKOLOGI KOMUNITAS: STUDI DI PONDOK PESANTREN - Ahmadi, Anas (Paramasastra, 2019)
This study aims to describe the implementation of creative writing in the perspective of community psychology at Tebu Ireng Islamic Boarding School, Jombang. This research is a study that uses qualitative methods because it narrates and describes the process of creative writing activities in the perspective of community psychology at the Tebu Ireng Islamic Boarding School. The results and discussion of the research in this study relate to the process of creative writing, namely pre-writing, writing process, and post-writing. Based on the results of questionnaires and interviews, it was concluded that participants gained new knowledge in writing, especially writing psychological perspectives.